Global Distribution and Spectral Properties of Low‐Reflectance Material on Mercury. Issue 7 (6th April 2018) - Klima, Rachel L.; Denevi, Brett W.; Ernst, Carolyn M.; Murchie, Scott L.; Peplowski, Patrick N.
Abstract: We examine the global distribution and spectral properties of low‐reflectance material (LRM) across Mercury to estimate the relative carbon abundance of prominent exposures and to test hypotheses for the origin of carbon in LRM. Our mapping demonstrates that LRM is consistently excavated from depth and that the spectral curvature attributed to carbon becomes more subdued as these surface deposits age. We find that the 600‐nm band depth in LRM deposits is related to carbon content and can be used to estimate carbon enrichment. LRM deposits excavated by basins and large craters may be enriched with as much as 4 wt% carbon over the local mean. Regional deposits, associated with the most heavily cratered terrains, are enriched by an average of ~2.5 wt% carbon. The association of LRM with excavation from depth shows that the carbon in LRM is native to the planet, rather than deposited over time by impacts. Plain Language Summary: Mercury's surface was revealed by the MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER) mission to be darkened, at least in part, by carbon. We explore the distribution and spectral properties of low‐reflectance material (LRM), the darkest and most carbon‐rich material on Mercury's surface, to test hypotheses for the origin of carbon on Mercury. Our mapping demonstrates that LRM is consistently excavated from depth. We find that LRM deposits excavated by basins and large craters may be enriched with as much as 4 wt% carbon over the local mean. Regional deposits, associated with the most heavily cratered terrains, are enriched by an average of ~2.5 wt% carbon. The association of LRM with excavation from depth suggests that the carbon in LRM is native to the planet, rather than deposited over time by impacts. Key Points: Low‐reflectance material on Mercury is excavated from depth The broad 600‐nm band depth in low‐reflectance material on Mercury is related to carbon content Carbon on Mercury is likely endogenic rather than exogenic